Money and Information - Berentsen, Aleksander; Rocheteau, Guillaume (Review of Economic Studies, 2004)
This paper investigates the role of money in markets in which producers haveprivate information about the quality of the goods they supply. When the fractionof high-quality producers in the economy is given, money promotes the productionof high-quality goods, which improves the quality mix and welfare unambiguously.When this fraction is endogenous, however, we find that money can decreasewelfare relative to the barter equilibrium. The origin of this inefficiency is thatmoney provides consumption insurance to low-quality producers, whichcan result in a higher fraction of low-quality producers in the monetaryequilibrium. Finally, we find that most often agents acquire more costlyinformation in the monetary equilibrium than in the barter equilibrium.Consequently, money is welfare-enhancing because it promotes usefulproduction and exchange, but not because it saves information costs. Copyright The Review of Economic Studies Limited, 2004.